RELASI GENDER DALAM ISLAM : TINJAUAN SOSIAL POLITIK - Wahidah Zein br Siregar (Pusat Studi Gender dan Anak, 2020)
The 2010 population census shows that the total population of Indonesia is 237,641,326 and 207,176,162 people (87%) of whom are Muslims. To this fact, the conversation on Islam and its relation to many aspects of life is unavoidable, including the gender relation, i.e., the social role, traits or characters that society attach to women and men. The change in social, economic and political life have forced Muslim women to take part and to pursue careers in various fields, so they spend quite a lot of time outside the home. This fenomena, to some extend, bring to the consequence of problems of women-men relation in Islamic community, albeit the lucidity of Qur’anic and hadis message on the equality of the two before Allah. This paper aims to describe gender relation, the relation between men and women in Indonesian Muslim society from a socio-political perspective, which means to lie the data on the ideas, experiences, and beliefs as well as the social-political theories existed in the society. Highlighting how Islamic gender relation is in accordance with those shown by Muslims in their daily lives. Also, examining how the ebb and flow of debates about women's participation in formatting their ‘self’, their families, societies, and this country. In order to answer the social problems arise from this gender inequality, this paper offer a comprehensive approach of solution, starting from Individual approach, Interactional approach until Institutional approach. All these methods will make it possible to apply different theories to save the society from the condition of “Sick Society”.